SOSIALISASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN SEJARAH MELALUI MEDIA FILM DI SMA NEGERI 6 PALU - Mutawakkil Mutawakkil; Junarti Junarti; Priyatna Prasetyawati; Nuraedah Nuraedah; Mubarak Mubarak (Jurnal Abdimas Bina Bangsa, 2022)
The problem with this community service is whether through this service, teachers and students can work together by using film media to shape student character in learning history in a public high school 6 Palu?  The goals that can be achieved in this service are (a) Film media is well documented and is expected to be a source of learning for students in a public high school 6 Palu, (b) Film media can be a source of inspiration in learning, (c) films can be well selected, starting from historical documentaries such as the proclamation events and contemporary historical events. The hope to be achieved through this community service is that teachers and students can synergize in the process of learning history to increase competence not only knowledge, but students' attitudes and character are also balanced and increase teacher competence in teaching creativity. Through outreach, mentoring and tracking in the form of observations, interviews and documents, it is hoped that teachers and students will have responsive and strong characteristics